Mediation in Household Dispute Reconciliation: Prospects and Challenge - Eneng Nuraeni; Ramdani Wahyu Sururi (Khazanah Hukum, 2022)
Domestic disputes are disputes within the family environment. Family disputes are personal disputes that do not need to be exposed. The settlement of household disputes must prioritize the restoration of the situation to maintain good relations in the family order. Mediation is an effective way to resolve household disputes because mediation is a peaceful dispute resolution that accommodates common interests, ensures the confidentiality of both parties, is cooperative, consensual and a win-win solution. However, although mediation is an effective method and is a method that is guided by the Qur'an (Qur'an 4:35), in reality, mediation has not become the main choice. The method used is a descriptive analysis method with a normative juridical approach. Observations show that mediation is an ideal alternative for resolving household disputes because it prioritizes peace and restoration of good relations (reconciliation) in family ties. There are several ways to make mediation in household dispute resolution effective, including not violating the general principles of ADR (Alternative Dispute Resolution), strengthening the role/function of mediators and maximizing the skills of mediators. The challenges of mediation as an alternative for resolving household disputes are; socialization of mediation institutions has not been optimal, there is still a lack of certified mediators, not yet qualified mediator skills/skills, the level of conflict is quite severe, there is no good faith, peace agreements do not have legal force, mediation in court is not based on volunteerism but based on procedural lawsuits. Thus, there needs to be a concrete effort to make mediation a reconciliation of household disputes, including from the parties, mediators and regulations on mediation.